SERVICE AS A FACTOR OF TERRITORIAL ORGANIZATION OF SOCIETY (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
The scientific mechanism of the service, developed on the idea of noosphere, creates conditions through its differentiated approaches for the following: reconstruction and greater sustainability oecumene's social life space structures, creation of social life's sustainable space systems through "service hubs" in wildlife. For the purpose of addressing these issues, it is necessary to use scientifically grounded mechanisms for creation and improvement of the forms of social life through Services sector activity.
Keywords: hypothesis; service; object; subject; humanization; complexity; human capital